Studi Persepsi dan Strategi Mahasiswa Pendidikan Biologi Universitas Labuhanbatu dalam Meraih Prestasi Akademik di Perguruan Tinggi - Siti Kholizah; Zunaidy Abdullah Siregar (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Student academic achievement is closely related using the cumulative achievement index.This study aims to determine the factors that influence the academic achievement of biology education students.This research method is descriptive qualitative. The data collection technique used in this study was a questionnaire.The sample of this study was 35 biology education students of Labuhanbatu University in semester seven in the 2022/2023 academic year.The sampling technique uses the stratified sampling technique, which is sampling according to the level of the cumulative achievement index range biology education students class of 2019 are <3.0-3.5 and >3.5. The data obtainedbe analyzed using qualitative data analysis techniques.The results of the study show that internal and external factors affect student learning achievement.The data obtained shows that internal factors affect academic achievement, namely interest indicators of 75-85% and other factors, namely attitudes, physical conditionand intellectual, with an average percentage with 71-82%, while the external influencing factor is the family indicator by 90-100%,andother factors, namely friends, lecturers, social environment, and infrastructure with an average percentage of 79-88%.